Hepatitis C infection among men who have sex with men living with HIV in New York City, 2000–2015. (4th December 2019) - Gabai, Claudia Michelle; Moore, Miranda S; Penrose, Katherine; Braunstein, Sarah; Bocour, Angelica; Neaigus, Alan; Winters, Ann
Abstract : Objectives: To calculate the rate of hepatitis C virus (HCV) among HIV-infected men who have sex with men (MSM) with no reported history of injection drug use (IDU), and to assess whether disparities exist in HIV/HCV coinfection by race/ethnicity and neighbourhood poverty level within this population in New York City. Methods: HIV-positive men who reported sex with men and did not report IDU at the time of HIV diagnosis, diagnosed through 2015 and alive as of 2000, were matched to people with HCV first reported to the New York City Department of Health and Mental Hygiene between 2000 and 2015. Those with HCV reported before or within 90 days of HIV infection were excluded. A multivariable Cox proportional hazards model was fit to compare the association between HCV diagnosis, race/ethnicity and neighbourhood poverty level. Results: From 2000 to 2015, 54 488 non-IDU MSM were diagnosed with HIV, of whom 2762 (5.1%) were diagnosed with HCV after HIV diagnosis, yielding an overall age-adjusted HCV diagnosis rate of 512 per 100 000 person-years. HIV/HCV coinfection was significantly higher among non-Latino blacks (adjusted HR (aHR)=1.24, 95% CI 1.11 to 1.40) compared with non-Latino whites and among persons living in high-poverty neighbourhoods compared with those in low-poverty neighbourhoods (aHR=1.17, 95% CI 1.01 to 1.35) after stratification by year of HIV diagnosis. Conclusion: Disparities in HIV/HCV coinfection among HIV-positive MSM were observed by race/ethnicity and neighbourhood poverty level. Routine HCV screening is recommended for people infected with HIV. People coinfected with HIV and HCV should be linked to HCV care, treated and cured to reduce morbidity and mortality, and to avoid ongoing HCV transmission.